Where Has All the Foreign Investment Gone in Russia? - Broadman, Harry G.; Recanatini, Francesca (World Bank, Washington, DC, 2014)
Since its transition to a market economy began, Russia has not attracted much foreign direct investment (FDI). Inflows of FDI into Russia are much lower than those into other transition countries in the region, adjusted for population size and similar measures. Clearly, if Russia is to grow it must increase the level of FDI inflows, which is why a good deal of policy attention has focused on the problem. Equally important for achieving sustainable growth in such a large, heterogeneous economy is learning how to make the spatial distribution of FDI within Russia more even. Inflows are strikingly skewed. Close to 60 percent of FDI goes to four regions in te western part of the country--Moscow City, Moscow oblast, St. Petersburg, and Leningrad oblast--which account for only 22 percent of Russia's gross national product and only 13 percent of Russia's population. Only two of the other 85 regions account for more than 2.5 percent of the country's FDI and most account for much less. Surprisingly, neither policymakers nor observers and analysts have paid much attention to diagnosing the reason for this imbalance in FDI's distribution. The authors try to empirically unbundle the determinants of FDI's regional distribution within Russia. They find that faactors associated with market size, infrastructure development, and the policy environment seem to explain much of the observed variation in FDI flows to regions in Russia. Moreover, the explanatory power of the model that best explains cross-regional variation in FDI flows from 1995 to 1998 changes significantly after the 1998 default and ruble devaluation--suggesting the possibility of a "structural change" in the determination of FDI after the 1998 crisis.